Implementation of Probolinggo Local Wisdom-Based Problem-Based Learning Model to Improve the Science Literacy Skills of High School Students - Arrafi, Wadhifah Qiyyamul Lailli; Wasis, Wasis; Ningsetyo, Maya; Amiruddin, Mohd Zaidi Bin; Desysetyowati, Novita; Sunarti, Titin (Physics Education Research Journal, 2023)
The characteristics of learning in the 21st century are directed at encouraging students to work together, be communicative, think creatively, think critically, think computationally, and have compassion. This study aims to apply a problem-based learning (PBL) model based on Probolinggo local wisdom to improve students' scientific literacy skills. The type of research used is quasi-experimental and uses a Nonequivalent Control Group Design. The type of research used is quasi-experimental and uses a Nonequivalent Control Group Design. This study used two class samples, namely class XII MIPA 1 as a class that will be given treatment (experimental) while class XII MIPA 3 as a class that is not given treatment (control). The Probolinggo local wisdom-based PBL model becomes the independent variable in this study. The dependent variable in this research is students' scientific literacy skills. The control variables in this study were the teachers or researchers, the number of students taught (sample), and the learning materials for dynamic fluids. This research obtained valid learning tools with a validity level of 89.2%. The level of implementation of learning is 94%. Applying learning to apply Probolinggo local wisdom-based PBL model effectively increases students' scientific literacy abilities. This was obtained from the results of the independent-sample T-test, showing that the significance value is 0.000, which is less than 0.05. An increase was seen from the N-Gain test, obtained 0.60 in the class that was given the treatment, while 0.05 in the class that was not. In the future, learning based on Probollinggo's local wisdom can be developed in dynamic fluid learning and linear material learning.